A polytetrafluoroethylene composite film material and a method for producing the same
Patent Information
- Application Number
- CN202610487436.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-14
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-04-14
AI Technical Summary
现有聚四氟乙烯复合膜材料在实际使用中仍可能存在疏水性能衰减、老化后性能保持不足以及阻隔效果不稳定等问题
[0037] 1. Compared with existing technologies, this invention uses polytetrafluoroethylene (PTFE) as the matrix and combines it with fluorinated resin, fillers, antioxidants, UV absorbers, and lubricants to construct a composite formulation system. This ensures the intrinsic properties of the PTFE material while also considering processing stability and performance in use. Specifically, the fluorinated resin improves the processing adaptability of the composite system, the antioxidants and UV absorbers help slow down performance degradation during use, and the lubricant facilitates subsequent mixing, curing, and paste extrusion processes. This results in a PTFE composite film material with good hydrophobic properties, aging resistance, and barrier properties.
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a polytetrafluoroethylene composite membrane material and its preparation method. Background Technology
[0002] Polytetrafluoroethylene (PTFE) composite membrane materials belong to the field of polymer membrane materials. PTFE itself possesses good chemical corrosion resistance, weather resistance, electrical insulation, and surface properties, thus having a solid foundation for application in functional membrane materials. As the application scenarios of membrane materials continue to expand, related research is no longer limited to maintaining the intrinsic properties of the material, but is gradually shifting towards the synergistic improvement of the overall performance of the membrane material, enabling it to maintain both good structural stability and service reliability under long-term use conditions.
[0003] Currently, these materials are mainly targeted at applications requiring high hydrophobicity, aging resistance, and barrier properties. Corresponding research focuses primarily on improving the overall performance of the membrane and enhancing its performance retention. While the preparation technology for polytetrafluoroethylene (PTFE) composite membranes is relatively mature, in practical applications, the membranes may still experience issues such as decreased hydrophobicity, insufficient aging resistance, and unstable barrier properties, making it difficult to simultaneously meet multiple performance requirements.
[0004] CN1566204A discloses a method for preparing a moisture-permeable virus-barrier polytetrafluoroethylene (PTFE) composite membrane. This method involves coating a moisture-permeable polyurethane or block polyether ester solution onto the surface of a biaxially stretched microporous PTFE membrane, followed by drying and peeling to form the composite membrane, thereby improving its virus-barrier performance. CN102068924B discloses a PTFE composite membrane and its preparation method. This method involves setting an adhesive layer between a support layer and a PTFE layer, and utilizing a porous polymer to infiltrate both layers to form a hinged amorphous network structure, thereby improving the composite membrane's peel strength and service life. CN107537327B discloses a PTFE membrane and its preparation method. This method constructs a three-dimensional interconnected porous structure formed by crisscrossing beaded fibers, creating a large number of rough structures on the membrane surface, resulting in a surface water contact angle greater than 165°, thus improving the membrane material's superhydrophobic properties. Existing polytetrafluoroethylene composite membrane materials may still have problems such as hydrophobicity degradation, insufficient performance retention after aging, and unstable barrier effect in actual use. Summary of the Invention
[0005] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a polytetrafluoroethylene composite membrane material and a method for preparing the same. By modifying the surface of the filler, the compatibility, interfacial bonding force and dispersibility between the filler and the polytetrafluoroethylene body are improved, thereby enhancing the hydrophobicity, aging resistance and barrier properties of the membrane material.
[0006] To achieve the above objectives, the present invention provides a polytetrafluoroethylene composite membrane material, characterized in that it comprises polytetrafluoroethylene, fluorinated resin, filler, antioxidant, ultraviolet absorber, and lubricant.
[0007] A polytetrafluoroethylene composite membrane material comprises the following raw materials, by weight: 100 parts polytetrafluoroethylene and 8-16 parts fluorinated resin.
[0008] 8-12 parts of filler
[0009] Antioxidant 0.01-0.2 parts
[0010] 0.01-0.2 parts of ultraviolet absorber
[0011] 15-20 parts lubricant;
[0012] Preferably, a polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 12-14 parts fluorinated resin.
[0013] 10-11 parts of filler
[0014] Antioxidant 0.01-0.1 parts
[0015] 0.01-0.1 parts of ultraviolet absorber
[0016] 17-18 parts of lubricant; wherein the filler is at least one of silica, talc, and mica powder;
[0017] The antioxidant is at least one of hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants; preferably, the antioxidant is at least one of Irganox®1010, Irganox®1076, Irganox®245, Irgafos®168, ADK STAB AO-60, and ADK STAB 2112.
[0018] The ultraviolet absorber is at least one of dihydroxybenzophenone, hydroxybenzotriazole, hydroxyphenyltriazine, or oxaloylaniline; preferably, the ultraviolet absorber is Tinuvin. ® 326. Tinuvin ® 1577, Tinuvin ® At least one of ADK STAB LA-31, ADK STAB LA-36, ADK STAB LA-46, ADK STAB LA-F70, and ADK STAB 1413.
[0019] The lubricant is at least one of naphtha, isoalkane, or dearomatic solvent oil; preferably, the lubricant is at least one of Super VM&P Naphtha, Isopar™ E, Isopar™ G, Isopar™ H, or Exxsol™ D80.
[0020] When preparing polytetrafluoroethylene (PTFE) composite membrane materials using fillers, problems often arise such as insufficient compatibility between the filler and the PTFE matrix, weak interfacial bonding, and poor dispersion uniformity. Due to the lack of an effective interfacial transition layer between the filler surface and the matrix, the filler is prone to local agglomeration or weak interfacial regions within the membrane. This not only hinders stress transfer but also makes the membrane a preferred pathway for moisture penetration and defect propagation under aging or humid and hot environments, thus limiting the membrane's hydrophobicity retention, aging resistance, and barrier properties. Therefore, this invention replaces ordinary fillers with modified fillers to improve the surface properties of the filler, enhance the interfacial interaction between the filler and the PTFE matrix, and improve the dispersion stability of the filler in the system.
[0021] More preferably, the filler can also be a modified filler; the preparation method of the modified filler includes the following steps:
[0022] (1) Place 80-120 parts by weight of mica powder at 100-110℃ and dry for 2-4 hours. Then add 500-700 parts by weight of an ethanol aqueous solution with a volume fraction of 70%-90% and sonicate for 20-40 minutes. Stir mechanically for 20-40 minutes to obtain a dispersion.
[0023] (2) Add 1-5 parts by weight of organic interface modifier to the dispersion and stir at room temperature for 1-3 hours. Then add 8-12 parts by weight of ammonia water with a mass fraction of 20%-30% to adjust the pH of the system to 9-11. Then add 60-100 parts by weight of tetraethyl orthosilicate ethanol solution with a mass fraction of 10%-20% and react at 25-35°C for 3-5 hours. After the reaction is completed, centrifuge, wash and dry to obtain loaded mica.
[0024] (3) Add the loaded mica to 400-600 parts by weight of anhydrous ethanol and mix evenly. Add 2-6 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 60-70℃ for 1-3 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0025] The organic interface modifier is at least one of tannic acid, branched polyethyleneimine, and dopamine; preferably, the organic interface modifier is a mixture of branched polyethyleneimine and dopamine in a mass ratio of (1-3):(1-3).
[0026] By employing modified fillers, a relatively stable modified layer is constructed on the filler surface through the synergistic effects of organic interface modification, tetraethyl orthosilicate loading, and fluorinated silane treatment. On one hand, this modified layer helps improve the bonding strength between the filler and the polytetrafluoroethylene (PTFE) matrix, reducing interfacial defects and micropores. On the other hand, the introduction of fluorinated components helps reduce the surface energy of the filler, further enhancing the hydrophobicity and its retention on the membrane surface. Therefore, after replacing ordinary fillers with modified fillers, the resulting PTFE composite membrane material exhibits better aging resistance, higher hydrophobicity retention, and lower water vapor permeability, effectively improving the technical defects of ordinary filler systems, such as poor interfacial bonding, rapid performance degradation, and insufficient barrier effect.
[0027] When branched polyethyleneimine is used in combination with dopamine, the branched polyethyleneimine molecular chain contains more amino groups, which helps to increase the number of active sites on the mica surface; dopamine, on the other hand, is more likely to form a stable adhesion layer on the mica surface. The synergistic effect of the two results in a more uniform and robust loading of subsequent tetraethyl orthosilicate, and provides a stable surface foundation for further processing with perfluorooctyltriethoxysilane, thereby reducing discontinuities and weak interfacial areas in the modified layer. Based on this, the interfacial bonding between the modified filler and the polytetrafluoroethylene body is improved, thus enhancing the aging resistance, hydrophobicity, and barrier properties of the resulting composite membrane material.
[0028] This invention also discloses a method for preparing a polytetrafluoroethylene composite membrane material.
[0029] A method for preparing a polytetrafluoroethylene composite membrane material includes the following steps:
[0030] S1 consists of polytetrafluoroethylene, fluorinated resin, filler, antioxidant, ultraviolet absorber, and lubricant;
[0031] S2 First, dry the filler at 100-110℃ for 3-6 hours;
[0032] S3 then adds polytetrafluoroethylene, fluorinated resin, filler, antioxidant and UV absorber into the mixer and mixes at 400-500 rpm for 10-40 minutes to obtain dry mix;
[0033] S4 Add lubricant to the dry mixture and continue mixing for 10-30 minutes, then seal and mature for 20-26 hours;
[0034] S5 pre-presses the matured material into a preform at 10-12MPa, and then extrudes the paste at 30-40℃ to obtain the initial film preform.
[0035] S6 calenders the initial film preform to 0.22-0.28mm, then degreases it by holding it at 70-90℃ for 10-30min and at 150-170℃ for 40-60min. After degreasing, it is preheated at 290-310℃ for 30-50s, stretched longitudinally by 2.5-3.0 times, then stretched transversely by 1.8-2.2 times, and then heat-set at 360-380℃ for 60-90s. After natural cooling, it is wound up to obtain the polytetrafluoroethylene composite film material.
[0036] The beneficial effects of this invention are:
[0037] 1. Compared with existing technologies, this invention uses polytetrafluoroethylene (PTFE) as the matrix and combines it with fluorinated resin, fillers, antioxidants, UV absorbers, and lubricants to construct a composite formulation system. This ensures the intrinsic properties of the PTFE material while also considering processing stability and performance in use. Specifically, the fluorinated resin improves the processing adaptability of the composite system, the antioxidants and UV absorbers help slow down performance degradation during use, and the lubricant facilitates subsequent mixing, curing, and paste extrusion processes. This results in a PTFE composite film material with good hydrophobic properties, aging resistance, and barrier properties.
[0038] 2. Compared with the prior art, the present invention improves the problems of poor compatibility, weak interfacial bonding and insufficient dispersion between the filler and polytetrafluoroethylene body by introducing modified filler into the polytetrafluoroethylene composite membrane material, thereby helping to reduce internal interface defects of the membrane material and improve the overall structural stability of the material. Detailed Implementation
[0039] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0040] The polytetrafluoroethylene (PTFE) was designated POLYFLON™ PTFE F-106 and purchased from Daikin Industries, Ltd.
[0041] The fluorinated resin is model Teflon™ FEP 9495, purchased from The Chemours Company.
[0042] The antioxidant is a commercially available product, model number Ir (parts by weight) anox ® 1010, purchased from BASF;
[0043] The lubricant was a commercially available product, model Isopar™ E, purchased from ExxonMobil Chemical.
[0044] The UV absorber is a commercially available product, model ADK STAB LA-F70, purchased from ADEKA Corporation.
[0045] Branched polyethyleneimine is a commercially available product, model number P434400, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0046] The mica powder is a commercially available product, 1250 mesh.
[0047] Other raw materials not mentioned are all common raw materials. The above content is only for the purpose of illustrating the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them themselves.
[0048] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0049] Example 1
[0050] A polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 14 parts fluorinated resin.
[0051] 11 parts of filler
[0052] Antioxidant 0.08 parts
[0053] 0.08 parts of ultraviolet absorber
[0054] 18 parts lubricant
[0055] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0056] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0057] (2) Add 10 parts by weight of 25% ammonia water to the dispersion and adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution and react at 30°C for 4 hours. After the reaction is completed, centrifuge, wash and dry to obtain loaded mica.
[0058] (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0059] The above raw materials are used to prepare polytetrafluoroethylene composite membrane materials, specifically including the following steps:
[0060] S1. Weigh out polytetrafluoroethylene, fluorinated resin, filler, antioxidant, ultraviolet absorber and lubricant respectively;
[0061] S2. The modified filler is dried at 105°C for 3 hours;
[0062] S3. Add polytetrafluoroethylene, fluorinated resin, filler, antioxidant and ultraviolet absorber to the mixer and mix at 450 rpm for 25 min to obtain dry mix;
[0063] S4. Add lubricant to the dry mixture and continue mixing for 20 minutes, then seal and mature for 24 hours;
[0064] S5. The matured material is pre-pressed into a preform at 11MPa and then extruded as paste at 35℃ to obtain the initial film preform.
[0065] S6. After the initial film blank is rolled to 0.25mm, it is degreased by holding it at 80℃ for 20min and at 160℃ for 50min. After degreasing, it is preheated at 300℃ for 40s, stretched longitudinally by 2.8 times, then stretched transversely by 2.0 times, and then heat-set at 370℃ for 75s. After natural cooling, it is wound up to obtain the polytetrafluoroethylene composite film material.
[0066] Example 2
[0067] A polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 14 parts fluorinated resin.
[0068] 11 parts of filler
[0069] Antioxidant 0.08 parts
[0070] 0.08 parts of ultraviolet absorber
[0071] 18 parts lubricant
[0072] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0073] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0074] (2) Add 2 parts by weight of tannic acid and 1 part by weight of branched polyethyleneimine to the dispersion, stir at room temperature for 2 hours, then add 10 parts by weight of 25% ammonia water to adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution, react at 30°C for 4 hours, after the reaction is completed, centrifuge, wash and dry to obtain loaded mica;
[0075] (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0076] The preparation method of the polytetrafluoroethylene composite membrane material is the same as that in Example 1.
[0077] Example 3
[0078] A polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 14 parts fluorinated resin.
[0079] 11 parts of filler
[0080] Antioxidant 0.08 parts
[0081] 0.08 parts of ultraviolet absorber
[0082] 18 parts lubricant
[0083] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0084] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0085] (2) Add 3 parts by weight of tannic acid to the dispersion, stir at room temperature for 2 hours, then add 10 parts by weight of 25% ammonia water, adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution, react at 30°C for 4 hours, after the reaction is completed, centrifuge, wash and dry to obtain loaded mica;
[0086] (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0087] The preparation method of the polytetrafluoroethylene composite membrane material is the same as that in Example 1.
[0088] Example 4
[0089] A polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 14 parts fluorinated resin.
[0090] 11 parts of filler
[0091] Antioxidant 0.08 parts
[0092] 0.08 parts of ultraviolet absorber
[0093] 18 parts lubricant
[0094] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0095] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0096] (2) Add 3 parts by weight of branched polyethyleneimine to the dispersion, stir at room temperature for 2 hours, then add 10 parts by weight of 25% ammonia water, adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution, react at 30°C for 4 hours, after the reaction is completed, centrifuge, wash and dry to obtain loaded mica;
[0097] (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0098] The preparation method of the polytetrafluoroethylene composite membrane material is the same as that in Example 1.
[0099] Example 5
[0100] A polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 14 parts fluorinated resin.
[0101] 11 parts of filler
[0102] Antioxidant 0.08 parts
[0103] 0.08 parts of ultraviolet absorber
[0104] 18 parts lubricant
[0105] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0106] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0107] (2) Add 2 parts by weight of dopamine and 1 part by weight of branched polyethyleneimine to the dispersion, stir at room temperature for 2 hours, then add 10 parts by weight of 25% ammonia water to adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution, react at 30°C for 4 hours, after the reaction is completed, centrifuge, wash and dry to obtain loaded mica;
[0108] (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0109] The preparation method of the polytetrafluoroethylene composite membrane material is the same as that in Example 1.
[0110] Example 6
[0111] A polytetrafluoroethylene composite membrane material comprises the following raw materials, in parts by weight: 100 parts polytetrafluoroethylene and 14 parts fluorinated resin.
[0112] 11 parts of filler
[0113] Antioxidant 0.08 parts
[0114] 0.08 parts of ultraviolet absorber
[0115] 18 parts lubricant
[0116] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0117] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0118] (2) Add 3 parts by weight of dopamine to the dispersion, stir at room temperature for 2 hours, then add 10 parts by weight of 25% ammonia water, adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution, react at 30°C for 4 hours, after the reaction is completed, centrifuge, wash and dry to obtain loaded mica;
[0119] (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0120] The preparation method of the polytetrafluoroethylene composite membrane material is the same as that in Example 1.
[0121] Comparative Example 1
[0122] It is basically the same as Example 1, except that the filler is mica powder.
[0123] Comparative Example 2 is basically the same as Example 1, except that:
[0124] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0125] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0126] (2) Add 10 parts by weight of ammonia water with a mass fraction of 25% to the dispersion and adjust the pH to 10; then add 80 parts by weight of tetraethyl orthosilicate ethanol solution with a mass fraction of 15% and react at 30°C for 4 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0127] Comparative Example 3 is basically the same as Example 1, except that:
[0128] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0129] (1) Place 100 parts by weight of mica powder at 105°C and dry for 3 hours, then add 500 parts by weight of anhydrous ethanol and mix evenly.
[0130] (2) Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane to the system and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
[0131] Comparative Example 4
[0132] It is basically the same as Example 1, except that:
[0133] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0134] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0135] (2) Add 2 parts by weight of tannic acid and 1 part by weight of branched polyethyleneimine to the dispersion, stir at room temperature for 2 hours, and after the reaction is completed, centrifuge, wash and dry to obtain organically treated mica;
[0136] (3) The obtained organically treated mica was added to 500 parts by weight of anhydrous ethanol and mixed evenly. Then, 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane were added and reacted at 65°C for 2 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain the modified filler.
[0137] Comparative Example 5
[0138] It is basically the same as Example 1, except that:
[0139] The filler is a modified filler; the preparation method of the modified filler includes the following steps:
[0140] (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion.
[0141] (2) Add 2 parts by weight of dopamine and 1 part by weight of branched polyethyleneimine to the dispersion, stir at room temperature for 2 hours, and after the reaction is completed, centrifuge, wash and dry to obtain organically treated mica;
[0142] (3) The obtained organically treated mica was added to 500 parts by weight of anhydrous ethanol and mixed evenly. Then, 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane were added and reacted at 65°C for 2 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain the modified filler.
[0143] Test Example 1
[0144] The tests were conducted according to GB / T 1040.3-2006. Samples were cut into thin film tensile specimens, with the testing direction uniformly aligned with the longitudinal direction of the film. Before testing, the specimens were placed at 23±2℃ and 50±5% relative humidity for 24 hours. A universal testing machine was used, with the tensile speed set to 50 mm / min, and the tensile strength was recorded. Five parallel samples were tested for each group, and the average value was taken.
[0145] The contact angle was measured using a contact angle meter. The test environment was 23±2℃; 5µL of deionized water was added drop by drop, and the contact angle was read after the droplet stabilized for 10 seconds; five different locations were selected for testing for each sample, and the average value was taken. The larger the water contact angle, the better the hydrophobicity of the membrane material surface.
[0146] The tests were conducted according to GB / T16422.3-2022. A UVA-340 fluorescent ultraviolet lamp was used, and the cyclic conditions were set as follows: 8 hours of UV irradiation at 60℃, 4 hours of condensation at 50℃, for a total aging time of 500 hours. After aging, the samples were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours. The tensile strength and water contact angle of the samples were then measured, and the tensile strength retention rate and water contact angle retention rate were calculated.
[0147] Tensile strength retention rate (%) = Tensile strength after aging / Tensile strength before aging × 100%;
[0148] Water contact angle retention rate (%) = Water contact angle after aging / Water contact angle before aging × 100%;
[0149] Among them, the tensile strength before aging and the water contact angle before aging are both taken as the average test values of the unaged samples in the same batch.
[0150] Table 1. Test results of tensile strength retention and water contact angle retention of polytetrafluoroethylene composite membrane materials.
[0151] Example 1 82.6 91.2 Example 2 91.8 95.6 Example 3 89.7 93.5 Example 4 86.4 92.0 Example 5 93.6 96.8 Example 6 90.3 93.7 Comparative Example 1 71.8 82.6 Comparative Example 2 77.4 86.8 Comparative Example 3 79.1 88.9 Comparative Example 4 84.3 90.4 Comparative Example 5 87.1 91.7
[0152] Test Example 2
[0153] The cup method was used for testing in accordance with GB / T1037-2021. The test conditions were set at 38℃ and 90% relative humidity; the effective test area of the sample was 50cm², and the mass of water vapor passing through the sample per unit time was recorded to calculate the water vapor transmission rate, which is expressed in g / (m²·24h). Each group of samples was tested three times, and the average value was taken.
[0154] Table 2. Test results of water vapor transmission rate of polytetrafluoroethylene composite membrane materials.
[0155] Example 1 11.8 Example 2 8.3 Example 3 9.7 Example 4 10.4 Example 5 7.6 Example 6 9.0 Comparative Example 1 15.6 Comparative Example 2 13.4 Comparative Example 3 12.7 Comparative Example 4 10.9 Comparative Example 5 10.1
[0156] Comparative Example 1 directly used mica powder, resulting in weak interfacial bonding between the filler and the polytetrafluoroethylene body. Consequently, its mechanical and hydrophobic properties remained poor after aging, and water vapor permeated more easily along interfacial defects. Comparative Example 2 only underwent treatment with ammonia and tetraethyl orthosilicate, and Comparative Example 3 only underwent treatment with perfluorooctyltriethoxysilane. Both were single-step modifications, and although they showed some improvement compared to Comparative Example 1, the performance enhancement was limited due to insufficient interfacial layer construction. Example 1, based on tetraethyl orthosilicate loading, underwent further fluorine treatment, and its performance was significantly better than Comparative Examples 1-3. Examples 2 and 5, based on this, further added tannic acid and branched polyethyleneimine, and dopamine and branched polyethyleneimine, respectively, for pretreatment, making the subsequent loading layer and fluorine-containing layer more stable. Therefore, their tensile strength retention rate and water contact angle retention rate were further improved, and the water vapor permeability was further reduced. Based on the data in Tables 1-2, Example 5 showed the best performance, followed by Example 2. This indicates that under the conditions described in this study, the dopamine-branched polyethyleneimine complex system and the tannic acid-branched polyethyleneimine complex system are more conducive to forming a stable and dense modified interface than using tannic acid, branched polyethyleneimine, or dopamine alone. Among them, the former has a more significant synergistic promoting effect on subsequent surface loading and fluorination treatment, thus exhibiting the best overall performance. Its dispersion state and interfacial bonding state are also superior, resulting in overall performance that is significantly better than the comparative examples.
[0157] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A polytetrafluoroethylene composite membrane material, characterized in that, The raw materials include the following parts by weight: 100 parts polytetrafluoroethylene, 12-14 parts fluorinated resin, 10-11 parts filler, 0.01-0.1 parts antioxidant, 0.01-0.1 parts ultraviolet absorber, and 17-18 parts lubricant; The filler is a modified filler; (1) Place 80-120 parts by weight of mica powder at 100-110℃ and dry for 2-4 hours. Then add 500-700 parts by weight of an ethanol aqueous solution with a volume fraction of 70%-90% and sonicate for 20-40 minutes. Stir mechanically for 20-40 minutes to obtain a dispersion. (2) Add 1-5 parts by weight of organic interface modifier to the dispersion and stir at room temperature for 1-3 hours. Then add 8-12 parts by weight of ammonia water with a mass fraction of 20%-30% to adjust the pH of the system to 9-11. Then add 60-100 parts by weight of tetraethyl orthosilicate ethanol solution with a mass fraction of 10%-20% and react at 25-35°C for 3-5 hours. After the reaction is completed, centrifuge, wash and dry to obtain loaded mica. (3) Add the loaded mica to 400-600 parts by weight of anhydrous ethanol and mix evenly. Add 2-6 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 60-70℃ for 1-3h. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler. The organic interface modifier is composed of branched polyethyleneimine and dopamine mixed in a mass ratio of (1-3):(1-3).
2. The polytetrafluoroethylene composite membrane material as described in claim 1, characterized in that: The antioxidant is at least one of hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants.
3. The polytetrafluoroethylene composite membrane material as described in claim 1, characterized in that: The ultraviolet absorber is at least one of dihydroxybenzophenone ultraviolet absorbers, hydroxybenzotriazole ultraviolet absorbers, hydroxyphenyltriazine ultraviolet absorbers, or oxaloylaniline ultraviolet absorbers.
4. The polytetrafluoroethylene composite membrane material as described in claim 1, characterized in that: The lubricant is at least one of naphtha, isoalkanes, or dearomatic solvent oils.
5. The polytetrafluoroethylene composite membrane material as described in claim 1, characterized in that, Includes the following raw materials, by weight: 100 parts of polytetrafluoroethylene 14 parts of fluorinated resin 11 parts of filler Antioxidant 0.08 parts 0.08 parts of ultraviolet absorber 18 parts lubricant The filler is a modified filler; the preparation method of the modified filler includes the following steps: (1) Place 100 parts by weight of mica powder at 105℃ and dry for 3 hours. Then add 600 parts by weight of 80% ethanol aqueous solution, sonicate for 30 minutes, and mechanically stir for 30 minutes to obtain a dispersion. (2) Add 2 parts by weight of dopamine and 1 part by weight of branched polyethyleneimine to the dispersion, stir at room temperature for 2 hours, then add 10 parts by weight of 25% ammonia water to adjust the pH to 10; then add 80 parts by weight of 15% tetraethyl orthosilicate ethanol solution, react at 30°C for 4 hours, after the reaction is completed, centrifuge, wash and dry to obtain loaded mica; (3) Add the loaded mica to 500 parts by weight of anhydrous ethanol and mix evenly. Add 4 parts by weight of 1H,1H,2H,2H-perfluorooctyltriethoxysilane and react at 65°C for 2 hours. After the reaction is completed, centrifuge, wash and dry to obtain the modified filler.
6. A method for preparing the polytetrafluoroethylene composite membrane material as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Prepare polytetrafluoroethylene, fluorinated resin, filler, antioxidant, ultraviolet absorber and lubricant; S2. Dry the packing material; S3. Mix polytetrafluoroethylene, fluorinated resin, filler, antioxidant and ultraviolet absorber to obtain dry mixture; S4. Add lubricant to the dry mixture and continue mixing, and then perform a curing process; S5. Pre-press the matured material into a blank and then extrude the paste to obtain the initial film blank. S6. The initial film blank is sequentially subjected to calendering, degreasing, preheating, longitudinal stretching, transverse stretching, heat setting, cooling and winding to obtain polytetrafluoroethylene composite film material.
Citation Information
Patent Citations
Polytetrafluoroethylene composite membrane and preparation method thereof
CN102068924B
A polytetrafluoroethylene membrane and its preparation method
CN107537327B
Polytetrafluoroethylene microporous membrane as well as preparation method and application thereof
CN114272770A
Preparation method of PTFE film, PTFE film and flexible high-frequency high-speed copper-clad plate
CN117004065A
Selective permeable porous membrane and preparation method thereof
CN120059377A